Community Empowerment through the Use of Lemongrass (Cymbopogon citratus) Extract as an Anti-Mosquito Spray in Sikumpul Village - Wahab, Nooraya Zakia; Sudarsono, Widyana; Fakhira, Nurfiryal; Praptomo, Ari Mul; Jingga, Mughnia Lintang; Ramdhani, Roni; Wibowo, Bagas Ady; Efendi, Muhammad Farhan; Wahyuni, Anggitya; Azzahra, Amanda Aleyda Puteri; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Lemongrass (Cymbopogon citratus) is an easily obtainable plant that contains active compounds, such as citronellal and geraniol, which have been proven effective as mosquito repellents. This activity aims to introduce the production of mosquito repellent spray made from lemongrass extract to the community of Sikumpul Village, Banjarnegara Regency, through descriptive methods and direct demonstrations. The production process involves boiling lemongrass, adding lime juice, filtering, and mixing the lemongrass extract with alcohol in a 1:3 ratio. In addition to the demonstration, participants also received education on the benefits of lemongrass, how its active compounds work, and proper spray application techniques. The results of the activity showed high enthusiasm from the community to produce the spray independently, as the materials used are easily obtainable, safe, and do not leave harmful residues. This lemongrass- based spray innovation is expected to become a practical and sustainable solution for mosquito control in household environments, while reducing dependence on chemical insecticides.